Beating backsliding?: Episodes and outcomes of democratic backsliding in Indo-Pacific Asia in the period 1950-2022 - Croissant, Aurel; Hengge, Anna; Wintergerst, Carmen (Asian international studies review, 2024)
Abstract The paper presents the first comprehensive analysis of all episodes of backsliding in democratic regimes in Indo-Pacific Asia from 1950-2022. Based on the experience of this sample of cases, this paper aims to generate insights into why some Asian democracies are more resilient to this gradual decline in the quality of democratic institutions. Using Haggard and Kaufman’s framework of the “weak democracy syndrome” and the three different kinds of mechanisms of accountability that, in theory, can beat democratic backsliding, our analysis aims to show not only how but also when different accountability mechanisms succeed or fail in stopping autocratization.
Gesehen am 04.07.2024